Multipartite attitudes to enterprise: A comparative study of young people and place. (June 2020) - Parkinson, Caroline; Nowak, Vicky; Howorth, Carole; Southern, Alan
The article examines young people's attitudes towards enterprise, comparing prosperous and deprived neighbourhoods and two UK cities. Corpus linguistics analysis identified multi-layered attitudes and variations in how place prosperity and city affect attitudes. High interest in enterprise was associated with weaker place attachment and reduced social embeddedness. Young adults from prosperous neighbourhoods delegitimised other's enterprises; the 'deprived' sub-corpus included more fluid notions of enterprise legitimacy. Liverpool accounts contained stronger discursive threads around self-determination; Bradford accounts included greater problematising of entrepreneurship versus employment. An original Multipartite Model of Attitudes to Enterprise is presented consisting of four layers: attitudes to enterprise generally, attitudes legitimising particular forms of enterprise, attitudes to enterprise related to place and attitudes to enterprise related to self. The conclusion explains why policies and research need to be fine-grained and avoid uni-dimensional conceptualisations of attitudes to enterprise, or deterministic arguments relating entrepreneurship to specific types of places or backgrounds.